Solve for m (complex solution)
\left\{\begin{matrix}m=cx\text{, }&x\neq 0\text{ and }c\neq 0\\m\in \mathrm{C}\text{, }&x=c\text{ and }c\neq 0\end{matrix}\right.
Solve for m
\left\{\begin{matrix}m=cx\text{, }&x\neq 0\text{ and }c\neq 0\\m\in \mathrm{R}\text{, }&x=c\text{ and }c\neq 0\end{matrix}\right.
Solve for c
\left\{\begin{matrix}c=x\text{, }&x\neq 0\\c=\frac{m}{x}\text{, }&x\neq 0\text{ and }m\neq 0\end{matrix}\right.
Graph
Share
Copied to clipboard
cxx+cm=cxc+xm
Multiply both sides of the equation by cx, the least common multiple of x,c.
cx^{2}+cm=cxc+xm
Multiply x and x to get x^{2}.
cx^{2}+cm=c^{2}x+xm
Multiply c and c to get c^{2}.
cx^{2}+cm-xm=c^{2}x
Subtract xm from both sides.
cm-xm=c^{2}x-cx^{2}
Subtract cx^{2} from both sides.
-mx+cm=-cx^{2}+xc^{2}
Reorder the terms.
\left(-x+c\right)m=-cx^{2}+xc^{2}
Combine all terms containing m.
\left(c-x\right)m=xc^{2}-cx^{2}
The equation is in standard form.
\frac{\left(c-x\right)m}{c-x}=\frac{cx\left(c-x\right)}{c-x}
Divide both sides by c-x.
m=\frac{cx\left(c-x\right)}{c-x}
Dividing by c-x undoes the multiplication by c-x.
m=cx
Divide xc\left(-x+c\right) by c-x.
cxx+cm=cxc+xm
Multiply both sides of the equation by cx, the least common multiple of x,c.
cx^{2}+cm=cxc+xm
Multiply x and x to get x^{2}.
cx^{2}+cm=c^{2}x+xm
Multiply c and c to get c^{2}.
cx^{2}+cm-xm=c^{2}x
Subtract xm from both sides.
cm-xm=c^{2}x-cx^{2}
Subtract cx^{2} from both sides.
-mx+cm=-cx^{2}+xc^{2}
Reorder the terms.
\left(-x+c\right)m=-cx^{2}+xc^{2}
Combine all terms containing m.
\left(c-x\right)m=xc^{2}-cx^{2}
The equation is in standard form.
\frac{\left(c-x\right)m}{c-x}=\frac{cx\left(c-x\right)}{c-x}
Divide both sides by c-x.
m=\frac{cx\left(c-x\right)}{c-x}
Dividing by c-x undoes the multiplication by c-x.
m=cx
Divide xc\left(-x+c\right) by c-x.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}